Knowledge, attitude, beliefs and use of over the counter drug products among medical undergraduates - Rani, Mamta; Gupta, M. C. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Over the counter (OTC) drug products are available without prescription and considered safe, effective, affordable and easily accessible. Among medical students use of OTCs and even prescription drugs available as OTCs is increasing day by day. The objective of the study was carried out to assess the knowledge, attitude and beliefs about OTCs, their use, safety and regulatory issues of OTCs among medical undergraduates. Methods: A questionnaire-based study was conducted and 151 medical students participated in this study. A preformed and validated questionnaire consisting of 2 parts was used. Part 1 consisted of general information regarding OTCs and Part 2 consisted information about knowledge, attitude, beliefs and use of OTCs. Data were analyzed and the results were expressed as percentages. Results: 100% participating students were aware about OTCs. 70% used them a lot because of availability and belief on safety. Chemist was a good source of advice over minor medical problems according to 38% of students. Information to be read on drug label was known to 62.5% of them. Affordability and accessibility (84%) was the main reason for OTCs use. Common medications bought without prescription were antibiotics, antihistaminics (100%) and cough syrups (90%). Headache and fever (100%), acidity (91%) were common indications for OTC use. Common OTCs stored at home were painkiller, antacids and skin care products. Conclusions: All students though were aware of OTCs but had little knowledge of regulation and usage. Many prescription drugs were also available as OTCs. Medical students need to be educated and trained about OTCs and the related issues.